Factors influencing early recurrence of hepatocellular carcinoma after curative resection. Issue 8 (August 2020) - Zhu, Yu; Gu, Lingling; Chen, Ting; Zheng, Guoqun; Ye, Chao; Jia, Weidong
Objective: To identify the factors influencing early recurrence in patients with hepatocellular carcinoma (HCC) after curative resection. Methods: Clinical data for 99 patients with HCC undergoing curative resection were analyzed. The clinicopathological factors influencing early recurrence were analyzed by Cox regression. Results: Twenty-five of 99 patients (25.3%) suffered from early recurrence. There were significant differences between patients with and without recurrence in terms of tumor diameter, tumor capsular integrity, and preoperative alpha fetoprotein level. Cox regression analysis revealed that a tumor diameter >2.6 cm and preoperatively increased total bilirubin (TBL) level were risk factors for postoperative recurrence, while tumor capsular integrity had a protective effect on postoperative recurrence. After adjusting for preoperative TBL level and tumor capsular integrity, the risk of HCC recurrence was markedly increased in line with increasing tumor diameter in a non-linear manner. Conclusion: Tumor diameter >2.6 cm and preoperatively increased TBL level are associated with a higher risk of early recurrence after curative resection in patients with HCC, while tumor capsular integrity is associated with a lower risk of early recurrence.